2009
DOI: 10.1038/eye.2009.184
|View full text |Cite
|
Sign up to set email alerts
|

Is neuronal dysfunction an early sign of diabetic retinopathy? Microperimetry and Spectral Domain Optical Coherence Tomography (SD-OCT) Study in individuals with diabetes, but no diabetic retinopathy

Abstract: Purpose To elucidate changes in the neurosensory retina in the macular area, using spectral domain OCT and correlate with functional loss on fundus-related microperimetry, in patients with diabetes and no diabetic retinopathy compared with age-matched healthy volunteers. Methods This was a prospective study enroling 39 patients in each group. All patients underwent comprehensive dilated eye examination. The foveal thickness and the photoreceptor layer thickness at the foveal centre were measured using spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
125
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 29 publications
9
125
3
5
Order By: Relevance
“…In contrast, significant thinning and smaller layer index values were particularly observed for the OS in all macular regions when comparing MDR with DM eyes using a local analysis in our study. Contrary to a previous study reporting thinning of the photoreceptor layer thickness (IS/OS) at the foveal centre in DM age-matched subjects without retinopathy (mean age: 50.92 ± 4.75 years and 49.87 ± 5.50 years, in diabetics and controls), we observed thickening of the OS in younger DM age-matched participants (35 ± 10) compared to controls (34 ± 12) [61]. However, compared to few studies reporting changes in the outer retinal segment when comparing the macular thickness in diabetic participants with/without retinopathy and control participants without diabetes, our study suggests the neural damage in the outer retina may be predominantly located in the OS [60,61].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast, significant thinning and smaller layer index values were particularly observed for the OS in all macular regions when comparing MDR with DM eyes using a local analysis in our study. Contrary to a previous study reporting thinning of the photoreceptor layer thickness (IS/OS) at the foveal centre in DM age-matched subjects without retinopathy (mean age: 50.92 ± 4.75 years and 49.87 ± 5.50 years, in diabetics and controls), we observed thickening of the OS in younger DM age-matched participants (35 ± 10) compared to controls (34 ± 12) [61]. However, compared to few studies reporting changes in the outer retinal segment when comparing the macular thickness in diabetic participants with/without retinopathy and control participants without diabetes, our study suggests the neural damage in the outer retina may be predominantly located in the OS [60,61].…”
Section: Discussioncontrasting
confidence: 54%
“…Contrary to a previous study reporting thinning of the photoreceptor layer thickness (IS/OS) at the foveal centre in DM age-matched subjects without retinopathy (mean age: 50.92 ± 4.75 years and 49.87 ± 5.50 years, in diabetics and controls), we observed thickening of the OS in younger DM age-matched participants (35 ± 10) compared to controls (34 ± 12) [61]. However, compared to few studies reporting changes in the outer retinal segment when comparing the macular thickness in diabetic participants with/without retinopathy and control participants without diabetes, our study suggests the neural damage in the outer retina may be predominantly located in the OS [60,61]. Conversely, because the duration of disease was 22 years in the MDR group vs. 13 years in the DM group, outer retinal changes might be associated with long-term inner retinal pathology.…”
Section: Discussioncontrasting
confidence: 54%
“…2 Specifically, measures of neuroretinal function such as microperimetry, 3 frequency doubling perimetry (FDP), [4][5][6][7] and contrast sensitivity 8,9 reveal reduced retinal sensitivity in patients with diabetes and no to minimal DR compared with controls. Similarly, many studies have demonstrated structural alterations to the retina among patients with diabetes and minimal to no retinopathy, as evidenced by changes in foveal thickness, 3,10 retinal nerve fiber layer (NFL) thickness, 11,12 and inner retinal thickness. 13,14 The damage to retinal structure and function that occurs from DM suggests that retinopathy is part of the systemic sensory neuropathy that affects other nerves during DM.…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem studies in humans have revealed neuronal degeneration and apoptosis in retinas, mainly in the ganglion cell layer (5,6). Furthermore, use of the modern technique of spectral domain optical coherence tomography for retinal imaging (7) has shown thinning of the retinal nerve fiber (8,9) and photoreceptor layers (10) in diabetic subjects in vivo before any visible vascular lesions could be detected. In addition, thinning of the ganglion cell layer and inner plexiform layers has been reported in patients with mild diabetic retinopathy (11).…”
mentioning
confidence: 99%